2014
DOI: 10.1111/hdi.12137
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐induced thrombocytopenia due to heparin lock in a hemodialysis patient: A case report

Abstract: Heparin-induced thrombocytopenia (HIT) is a potentially fatal clinical condition which can develop after exposure to unfractionated or low-molecular-weight heparins. Even small doses of heparin such as heparin flushes in hemodialysis catheter can induce the development of HIT. However, the true incidence of heparin lock-related HIT is unknown. We report a 58-year-old woman with acute kidney injury because of obstructive uropathy who developed HIT after heparin-free hemodialysis. She was found to have severe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Second, the patients enrolled in the current study were taking various medications that might affect plasma XOR activity [ 40 ]; however, we could not take these differences into consideration owing to the relatively small sample size. Third, because XOR has affinity for heparin and can bind to vascular endothelial cells [ 41 ], administration of heparin before blood collection might increase XOR activity in the circulating blood; however, heparin injection was not performed before blood sampling in accordance with other investigators’ methods of XOR activity measurement [ 17 , 26 , 34 ], and also to avoid potential adverse effects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the patients enrolled in the current study were taking various medications that might affect plasma XOR activity [ 40 ]; however, we could not take these differences into consideration owing to the relatively small sample size. Third, because XOR has affinity for heparin and can bind to vascular endothelial cells [ 41 ], administration of heparin before blood collection might increase XOR activity in the circulating blood; however, heparin injection was not performed before blood sampling in accordance with other investigators’ methods of XOR activity measurement [ 17 , 26 , 34 ], and also to avoid potential adverse effects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies detailed the use of IVIG or TPE as initial therapy (see Table 2). Twelve studies included 13 case reports 46,[48][49][50][51][52][53][54][55][56][57][58] and one case series included four patients. 14 One case-controlled study of 44 patients reported aggregate data on 26 TPE-treated patients and is summarized separately.…”
Section: Treatment Indication 2: Initial Therapymentioning
confidence: 99%
“…Heparin was then discontinued and argatroban was started. Additionally, Chan et al [10] presented a case of 58-year-old woman with acute kidney injury was initiated on heparin-free hemodialysis. Subsequent thrombocytopenia development and positive HIT antibodies led to HIT type II diagnosis, and patient was eventually put on plasmapheresis.…”
Section: Discussionmentioning
confidence: 99%